A Comparative Hydrogeochemical Study of Granitic Fractured and Alluvial Channel Aquifer Systems (Global Journal of Science Frontier Research, 2014)
Hydrogeochemical investigations were carried out with the aim of assessing the geochemical water composition and processes governing groundwater hydrochemistry in Alluvial Aquifer of the Modder River catchment in Southern Africa and the granitic fractured Aquifer of Pallisa District in eastern Uganda. This was based on chemical analyses of water samples from existing wells and new boreholes in the two study areas. From the analyses, there were significant variations in the quality/composition of groundwater in the period of sampling. The calculated SAR, Na% and RSC values indicated that the water is of good quality and is suitable for drinking and irrigation purposes in the two study areas except for a few locations. Na and HCO3 are dominant with respect to the chemical composition of the groundwater. Detailed studies of the hydrogeochemical processes in the alluvial and granitic aquifer systems also shown that dissolution of silicate weathering, dolomite and calcite minerals, ion exchanges as well as anthropogenic influence to a lesser extent are the dominant hydrogeochemical processes that control groundwater quality. The increase in salinity is related to the dissolution of minerals in the host rocks and the evaporative concentration of solutes.
Keywords: hydrogeochemistry; granitic fractured; alluvial channel aquifer; wish; phreeqc model; pallisa district; modder river catchment